2023
DOI: 10.1002/jcpy.1374
|View full text |Cite
|
Sign up to set email alerts
|

Work with me or work for me: The effect of brand roles depends on implicit theories of self‐change

Abstract: Consumer‐brand relationships are important predictors of consumption, but the psychology surrounding the different roles brands occupy within these relationships is not fully understood. Three experiments and one field study investigate how preferences for two of these brand roles, partner and servant, depend on consumers' implicit theories of self‐change. Counter to what prior literature might suggest, findings show that consumers who believe that self‐traits are relatively malleable (incremental theorists) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…First, customer citizenship behavior is significantly higher for growth-(vs. fixed-) mindset customers. This aligns with the findings of previous studies that found that a growth mindset significantly impacts positive behaviors, such as value co-creation and benevolence (Jain et al, 2023;Rai et al, 2023). This is possible because these consumers not only voluntarily provide constructive feedback to improve the service quality of the employees but are also more resilient and forgiving in case of service failures.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…First, customer citizenship behavior is significantly higher for growth-(vs. fixed-) mindset customers. This aligns with the findings of previous studies that found that a growth mindset significantly impacts positive behaviors, such as value co-creation and benevolence (Jain et al, 2023;Rai et al, 2023). This is possible because these consumers not only voluntarily provide constructive feedback to improve the service quality of the employees but are also more resilient and forgiving in case of service failures.…”
Section: Discussionsupporting
confidence: 89%
“…A growth mindset is inclined to participate in sustainable behaviors as it tends to learn more about the organization's activities and brands (Rai et al, 2023). For example, such customers are more likely to purchase green food as they are highly conscious of their health (Ahn, 2022).…”
Section: Mindsets and Customer Citizenship Behaviormentioning
confidence: 99%
See 2 more Smart Citations